High School Students’ Perceptions Of Gerakan Literasi Sekolah - Diyahiyah Thotho Lansyah; Nurhadi Nurhadi; Bagas Narendra Parahita (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2023)
Gerakan Literasi Sekolah or GLS is a government-led movement through the Ministry of Education and Culture to organize literacy activities throughout school education. GLS focuses on developing character through reading book material by cultivating a literacy ecosystem at school. The purpose of the study was to determine the impact of GLS through students' understanding and perceptions of the program that has been undertaken. The approach method used in this research is descriptive qualitative data collection through teacher and student interviews at one of the high schools in Boyolali. The results showed that GLS is the result of policy mobilization from the government, with the issuance of Permendikbud Number 15 of 2015, which requires every school to organize GLS, and students are inevitably needed to carry out the regulation. In general, GLS in Indonesia is still at the stage of growing interest in reading. However, in its implementation, literacy is not implemented by the guidelines. The purpose of literacy still needs to be achieved as it should be. Students' perceptions and paradigms on literacy still include the meaning of reading and writing activities, students' awareness of reading needs to be improved, and GLS needs to be optimally integrated with GLK and GLM. However, overall, the school has been quite good in starting the stages of implementing GLS in their school.